The Slow Formation of Working-Class Neighborhoods in the Southwest Part of Santiago. the Efforts of the State and the Neighborhood Organizations, Dialogues and Disagreements (1920–1930); [la Lenta Formación de Barrios Obreros en el Sur Poniente de Santiago. el Esfuerzo Estatal y la Agencia Pobladora, Diálogos y Desencuentros (1920–1930)] - Venegas-Valdebenito, H; Morales-Barrientos, D (Universidad de Tarapaca, 2023)
The model working-class neighborhoods of Santiago originated a new way of inhabiting the city. When analyzing the different purposes of the elite to develop these residential complexes, the southwest part of the Santiago Municipality is distinguished as the most intervened by the habitational state policies and by the organizations that developed over time, which turned organized neighbors into a group of interest in the local space. In such space and organization, it is possible to notice the irregular occupation of their homes and the relationship that neighborhood committees had with local authorities between the 1920s and 1930s. © 2023, Universidad de Tarapaca. All rights reserved.
Keywords: adquiriente; asociatividad barrial; informal sociability; Model working-class neighborhood; mortgagor; neighborhood associations; Población modelo; sociabilidad informal